STUDI OPTIMALISASI KONFIGURASI STRUKTUR KUDA-KUDA ATAP BAJA RINGAN - Hazmal Herman; Ridho Aidil Fitrah; Sabril Haris (Racic : Rab Construction Research, 2018)
Roof truss of lightweight steel has been used for any types of construction. Functioned as the truss, this could makes variations of roof truss configuration which depended on construction necessity and performance on certain span. Then, this research analyzed the configurations for short span and intermediate span. The result will recommend roof truss configuration which used light weight steel. The analysis used software SAP 2000 v.19. The lightweight steel section is channel section of C 75.35.0,75 which is found on any store building. In general, the result of this analysis were tensile and compressive ratio which is obtained by comparison of internal force and section capacity. This calculation also referred to SNI 7971:2013 code. Then, tensile and compression ratio are obtained less than 0,9 for each configurations and spans. So, the structure are stable. However, Fink and Cremona configuration have considerable results which give the smallest tensile and compression ratio compared to another configurations for short span and intermediate span respectively. It can be concluded that Fink and Cremona were recommended for lightweight steel truss for short spans and intermediate spans. Lightweight steel section C 75.35.0,75 also can be used in this configuration.